Atomically dispersed Fe−N₄ and Ni-N₄ independent sites enable bidirectional sulfur redox electrocatalysis - Yang, Jin-Lin (2023)
Single-atom catalysts (SACs) with high atom utilization and outstanding catalytic selectivity are useful for improving battery performance. Herein, atomically dispersed Ni-N4 and Fe-N4 dual sites coanchored on porous hollow carbon nanocages (Ni-Fe-NC) are fabricated and deployed as the sulfur host for Li-S battery. The hollow and conductive carbon matrix promotes electron transfer and also accommodates volume fluctuation during cycling. Notably, the high d band center of Fe in Fe-N4 site demonstrates strong polysulfide affinity, leading to an accelerated sulfur reduction reaction. Meanwhile, Li2S on the Ni-N4 site delivers a metallic property with high S 2p electron density of states around the Femi energy level, enabling a low sulfur evolution reaction barrier. The dual catalytic effect on Ni-Fe-NC endows sulfur cathode high energy density, prolonged lifespan, and low polarization.